Ensaios de reação ao fogo de tintas intumescentes com granulado de cortiça - Mesquita, L.M.R. (2018)
This paper presents an experimental study about the fire protection efficiency of a material produced of an emulsion of intumescent coating with granulated cork. The analysis is performed at the micro scale level, with TG and DSC tests at elevated temperatures, and in a mass loss calorimeter with protected steel plates, with temperatures representative of a fire scenario. The results indicate that an increased protection is obtained when the granular cork particle size is smaller and a cork mass fraction of 5% is used